Tick paralysis induced by Ixodes gibbosus: enigmatic cases in domestic mammals from Cyprus - Diakou, Anastasia; Foucault-Simonin, Angelique; Antoniou, Giannakis; Cabezas-Cruz, Alejandro; Földvári, Gábor (Frontiers in Veterinary Science, 2024)
Tick paralysis is a potentially fatal condition caused by toxins produced and secreted by tick salivary glands. This survey presents clinical and epidemiological observations of tick paralysis cases in domestic animals in Cyprus. Local veterinarians report typical tick paralysis cases occurring in goats, sheep, dogs, and cats. The animals suffering from paralysis are free from other neurological diseases, have blood and biochemical parameters within normal ranges, and recover fast by simply removing the ticks found predominantly on the head and around the neck. Tick paralysis cases occur in a specific geographic area of Cyprus (Akamas peninsula), from September through March, but not every year. Instead, the phenomenon has 2 periodic cycles of occurrence, a 3-and a 7-year cycle. The two cycles are differentiated by severity based on the number of affected animals and the resulting losses. As described for other tick-borne diseases, these cyclic patterns may be attributed to external factors, selfoscillations of the disease system, or the combined action of these mechanisms. Ticks collected from a recent paralysis case in a goat were morphologically and molecularly identified as Ixodes gibbosus. Efforts should be made to characterise the specific toxins involved in tick paralysis and to develop a vaccine, which could prevent significant losses of small ruminants, especially in free-ranging farming systems, a prevalent management approach observed in Cyprus and various regions worldwide.